2020
DOI: 10.3390/en13102486
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of a Large Two-Stroke Engine Crankshaft Dynamics Model

Abstract: The crankshaft dynamics model is of vital importance to a multitude of aspects on engine diagnostics; however, systematic investigations of such models performance (especially for large two-stroke diesel engines that are widely used in the power generation and shipping industries) have not been reported in the literature. This study aims to cover this gap by systematically investigating the parameters that affect the performance of a two-stroke diesel engine crankshaft dynamics model, such as the numerical sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…The vibration of the crankshaft [44,45] during the measurement was not analyzed as the conditions are quasi-static. Due to the character of reaction forces, we did not discuss either any vibration model or any issues of structural dynamics of reciprocating engines [46][47][48][49][50]. The entire adjustment process is controlled by a computer-based monitoring application.…”
Section: Crankshaft Geometry Measuring Methodsmentioning
confidence: 99%
“…The vibration of the crankshaft [44,45] during the measurement was not analyzed as the conditions are quasi-static. Due to the character of reaction forces, we did not discuss either any vibration model or any issues of structural dynamics of reciprocating engines [46][47][48][49][50]. The entire adjustment process is controlled by a computer-based monitoring application.…”
Section: Crankshaft Geometry Measuring Methodsmentioning
confidence: 99%
“…This is due to the non-linearities introduced primarily by the large reciprocating and rotating masses of the engine's piston assembly. 43,66 It is observed that the measured ICT data sufficiently match the ICT from the extended model deployed within the inverse problem method. As shown in Figure 5(b), the residuals between these ICT variations fluctuate at approximately two orders of magnitude less than the measured ICT data, which demonstrates a very small difference.…”
Section: Individual Case Studies Analysismentioning
confidence: 84%
“…This larger system of equations is therefore solved using the a piecewise Linear Time-Invariant (LTI) system solver, which is the default solver for the direct model. 43 _…”
Section: Extended Direct Crankshaft Dynamics Modelmentioning
confidence: 99%
“…This model can be used as a dynamic excitation in simulation tests of torsional vibrations of crankshafts with a torsional vibration damper. The application of an excitation similar in nature to the real one will make it possible to fine-tune the damper parameters on the basis of a computer simulation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%